2021
DOI: 10.5114/hm.2021.106171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a smartphone use on dynamic balance in healthy adolescents

Abstract: Purpose. The aim of the study was to detect the immediate and late effects of using a smartphone for 30 consecutive minutes on dynamic balance in healthy adolescents. Methods. Overall, 96 healthy adolescents of both genders, aged 15-18 years, were randomly assigned to the study and the control group. The subjects in the study group used a smartphone for 30 consecutive minutes; smartphones were not allowed in the control group. A Biodex system was used to assess the dynamic balance initially, as well as immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Prolonged muscular tension alters the sensitivity of neck proprioception, affecting balance and resulting in postural instability [18]. This study's findings align with the findings of Shafeek et al [19], who investigated the impact of SP usage on dynamic balance in healthy adolescents, and their work revealed Md -mean difference, * significant values a significant immediate influence of SP use on balance. Moreover, our findings are comparable to those of Lee et al [20], who found that using an SP changes the degree to which healthy adults can control their posture.…”
Section: Discussionsupporting
confidence: 89%
“…Prolonged muscular tension alters the sensitivity of neck proprioception, affecting balance and resulting in postural instability [18]. This study's findings align with the findings of Shafeek et al [19], who investigated the impact of SP usage on dynamic balance in healthy adolescents, and their work revealed Md -mean difference, * significant values a significant immediate influence of SP use on balance. Moreover, our findings are comparable to those of Lee et al [20], who found that using an SP changes the degree to which healthy adults can control their posture.…”
Section: Discussionsupporting
confidence: 89%
“…Previous review studies reported limited evidence for some interventions for stroke patients including repetitive task training, exercise therapy, care-mediated exercise, physical fitness training, use of unstable support surfaces, and virtual therapy that may be effective in balance recovery after stroke. For confirming this finding, further research is recommended [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 80%
“…Research reports damage to such sensory system with stroke patients with a high rate of proprioception affection, which affects both static and dynamic postural stability. Therefore, evaluation by the clinical test of sensory interaction and balance (CTSIB) should be considered for both aspects of static and dynamic postural control by the ability to control the tilting angle of the Biodex platform [ 8 ].…”
Section: Introductionmentioning
confidence: 99%